Non-axisymmetric neoclassical transport from mis-alignment of equipotential and magnetic surfaces - Markl, M.; Heyn, M.F.; Kasilov, S.V.; Kernbichler, W.; Albert, C.G. (Problems of Atomic Science and Technology, 2022)
Coefficients of neoclassical transport in tokamaks and stellarators with non-axisymmetric equipotential surfaces mis-aligned with magnetic flux surfaces are derived for the 1/ν regime. In the general case, they are given by integral expressions including field line integrals similar to those defining the effective helical ripple [V.V. Nemov et al. // Phys. Plasmas. 1999, v. 6, p. 4622]. For small mis-alignments in a tokamak with a simplified geometry, they are reduced to simple analytical expressions.